(untitled) (Metallurgy and Foundry Engineering, 2007)
In the paper strain distribution in materials commonly referred to as soft materials (electrolytic copper 99,9 % Cu, annealed) and hard ones (steel 20, containing 0,2 % C) produced during hot upsetting process. Numerical calculations were performed with a use of commercial software QForm2D/3D. Significance of the influence of friction forces in the head surface on the free surface profile and distor-tion of rectangular coordination grid of deformations, as well as, effective strain distribution, in various stages of the process was investigated. The results indicate changes in nonuniformity of strain in obtained forgings.